Nasal Reconstruction after Mohs Cancer Resection: Lessons Learned from 2553 Consecutive Cases. Issue 1 (29th June 2021) - Halani, Sameer H.; Ma, Connie; Pierce, Joshua; Sanniec, Kyle; Thornton, James F.
Abstract : Background: Nasal defects following Mohs resection are a reconstructive challenge, demanding aesthetic and functional considerations. Many reconstructive modalities are available, each with varying utility and efficacy. The goal of this study was to provide an algorithmic approach to nasal reconstruction and illustrate lessons learned from decades of reconstructing Mohs defects. Methods: A retrospective review was conducted of consecutive patients who underwent nasal reconstruction after Mohs excision from 2003 to 2019 performed by the senior author (J.F.T.). Data were collected and analyzed regarding patient and clinical demographics, defect characteristics, reconstructive modality used, revisions, and complications. Results: A total of 2553 cases were identified, among which 1550 (1375 patients) were analyzed. Defects most commonly affected the nasal ala (48.1 percent); 74.8 percent were skin-only. Full-thickness skin-grafts were the most common reconstructive method (36.2 percent); 24.4 percent of patients underwent forehead flaps and 17.0 percent underwent nasolabial flaps. The overall complication rate was 11.6 percent ( n = 181), with poor wound healing being most common. Age older than 75 years, defects larger than 2 cm 2, and active smoking were associated with increased complication rates. Conclusions: Nasal reconstruction can be divided based on anatomical location, and an algorithmic approach facilitates excellent results. Although local flaps may be suitable for some patients, they are not always the most aesthetic option. The versatility and low risk-to-benefit profile of the forehead flap make it a suitable option for elderly patients. Although reconstruction is still safe to be performed without discontinuation of anticoagulation, older age, smoking, and large defect size are predictors of complications. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.